Genetic diversity and forensic parameters of 12 X-STR included in Argus X-12® marker panel in the population of the Russian Federation - Andrei Semikhodskii; Yevgeniy Krassotkin; Tatiana Makarova; Vladislav Zavarin; Viktoria Ilina; Daria Sutyagina (Annals of Human Biology, 2021)
Background X-chromosome specific short tandem repeats (X-STR) are indispensable for parentage analysis, kinship determination and forensic casework. Aim To determine allelic frequencies and forensic parameters of the 12 X-STR markers from the Investigator® Argus X-12® kit panel for the population of the Russian Federation. Subjects and methods We analysed 803 unrelated individuals from 58 localities across the Russian Federation. Intra-population genetic diversity was evaluated and comparison of the Russian population with 19 geographically distant populations performed. Results Heterozygosity values across all the loci ranged from 0.685 for DXS7423 to 0.939 for DXS10135. Deviations from the Hardy-Weinberg equilibrium were observed for DXS10074 (p < 0.05) and DXS10146 (p < 0.01). The value for power of discrimination across all the loci in males was 0.9999999996, while in females it equalled 0.9999999999. Combined mean exclusion chances MECKruger, MECKishida, MECD-trio, and MECD-duo were 0.9999988168, 0.9999999983, 0.9999999983, and 0.9999995797, respectively. Phylogenetic analysis indicated small genetic differences between the Russian population and the populations of neighbouring Lithuania, Belarus and the Slavic-speaking countries (Czech Republic, Serbia and Croatia). Conclusions This paper is the first report of forensically important parameters and allele frequencies for the 12 X-STR loci included in Argus X-12® marker system in the population of the Russian Federation.